La danza como manifestación rítmica para mejorar la autoestima en niños del cuarto grado de la unidad educativa Calasanz, Loja 2023 - Camacho Chuquimarca, Brian Steve (2024)
The present curricular integration work was directed to the general objective of implementing dance as a rhythmic manifestation to improve self-esteem in fourth grade students of the Calasanz Fiscomicional Educational Unit; it was an investigation of a mixed approach, of a correlational type, quasi-experimental design, the methods used are: scientific, deductive, inductive, analytical, synthetic and statistical, besides the observation technique and survey instruments, test and observation sheet. The Rosenberg test was applied with the sample of 30 students, at the moment of obtaining the results of the pre-test application it was evidenced that an 80% of the sample has high self-esteem and only a 20% shows that their self-esteem is medium; after the results obtained, a pedagogical proposal was implemented in order to improve the students’ self-esteem through the use of twenty previously structured planning, with the purpose of achieving the rhythmic manifestation through the different dance steps and making them to feel confident, developing skills of socialization and coexistence with their classmates and teacher. After carrying out the application of the proposal, the post-test was applied, validating the students self-confidence improvement, likewise the statistics indicate that the scale increases to 97% improvement and 3% is in a total development. It is concluded that in the pre-test the students had a good self-esteem and just a few students in the sample needed to work and improve; after the pedagogical intervention the results were positive, since it is validated that the confidence in the learners increases continuously, which shows that dancing is a strategy that helps to improve the students’ self-esteem, achieving socialization with the people who surround them and losing their fear of expressing themselves freely. Key Words: Dance, self-esteem, expression, manifestation, coexistence.